Kaplan's clinical hypertension - Kaplan, Norman M; Lieberman, Ellin; Neal, William (Lippincott Williams & Wilkins, 2002)
Univ. of Texas Southwestern Medical School, Dallas. Brandon/Hill Medical List first-purchase selection (#72). Latest information on the common problems in primary hypertension. Provides pathophysiology to permit sound clinical judgement. Previous edition, c1998, was titled Clinical Hypertension. DNLM: Hypertension.
Keywords: kardiologie; Hypertension; angiologie; hypertenze